2019
DOI: 10.4070/kcj.2018.0446
|View full text |Cite
|
Sign up to set email alerts
|

Development and Validation of Deep-Learning Algorithm for Electrocardiography-Based Heart Failure Identification

Abstract: Background and Objectives Screening and early diagnosis for heart failure (HF) are critical. However, conventional screening diagnostic methods have limitations, and electrocardiography (ECG)-based HF identification may be helpful. This study aimed to develop and validate a deep-learning algorithm for ECG-based HF identification (DEHF). Methods The study involved 2 hospitals and 55,163 ECGs of 22,765 patients who performed echocardiography within 4 weeks were study subj… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
53
1
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 87 publications
(59 citation statements)
references
References 28 publications
4
53
1
1
Order By: Relevance
“…Attia et al developed deep-learning algorithms for screening cardiac contractile dysfunction, predicting the occurrence of atrial fibrillation during sinus rhythm, approximating age and sex, and detecting hyperkalemia using raw ECG data and demonstrated its feasibility 11,12,24,25 . Our study showed that a deep-learning-based algorithm using ECG could outperform cardiologists in diagnosing left ventricular hypertrophy and valvular heart disease 14,15,26,27 . We used a sensitivity map to visualize the regions of the ECGs that were used for decision-making by the DLA.…”
Section: Discussionmentioning
confidence: 81%
“…Attia et al developed deep-learning algorithms for screening cardiac contractile dysfunction, predicting the occurrence of atrial fibrillation during sinus rhythm, approximating age and sex, and detecting hyperkalemia using raw ECG data and demonstrated its feasibility 11,12,24,25 . Our study showed that a deep-learning-based algorithm using ECG could outperform cardiologists in diagnosing left ventricular hypertrophy and valvular heart disease 14,15,26,27 . We used a sensitivity map to visualize the regions of the ECGs that were used for decision-making by the DLA.…”
Section: Discussionmentioning
confidence: 81%
“…Previous ECG-based methods for automated computer aided detection (CAD) of HF using various methodologies have achieved encouraging results. The duration of ECG signal recording was variable and could be as short as 2 s [10,[54][55][56][57][58]. Simple clinical prediction rules (CPR) for HF detection performed less well compared to ECG based methods [59].…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, feature extraction and model learning take place in a unified step in deep learning [9]. Deep learning-based approaches have become very successful in a wide range of biomedical analysis tasks [10], including the analysis of retinal fundus images [11], radiologic images [12], pathologic tissue images [13], electrocardiograms [14] and electroencephalograms [15]. However, deep learning-based methods generally require large annotated datasets compared to traditional machine learning [16].…”
Section: Introductionmentioning
confidence: 99%